Classification of Extrapulmonary Manifestations Due to Mycoplasma pneumoniae Infection on the Basis of Possible Pathogenesis - Narita, Mitsuo (Frontiers in Microbiology, 2016)
The list of extrapulmonary manifestations due to Mycoplasma pneumoniae infection can be classified according to the following three possible mechanisms derived from the established biological activity of M. pneumoniae; 1) a direct type in which the bacterium is present at the site of inflammation and local inflammatory cytokines induced by the bacterium play an important role 2) an indirect type in which the bacterium is not present at the site of inflammation and immune modulations, such as autoimmunity or formation of immune complexes, play an important role and 3) a vascular occlusion type in which obstruction of blood flow induced either directly or indirectly by the bacterium plays an important role. Recent studies concerning extrapulmonary manifestations have prompted the author to upgrade the list, including cardiac and aortic thrombi as cardiovascular manifestations; erythema nodosum, cutaneous leukocytoclastic vasculitis, and subcorneal pustular dermatosis as dermatological manifestations; acute cerebellar ataxia, opsoclonus-myoclonus syndrome, and thalamic necrosis as neurological manifestations; pulmonary embolism as a respiratory system manifestation; and renal artery embolism as a urogenital tract manifestation. Continuing nosological confusion on M. pneumoniae–induced mucositis (without skin lesions), which may be called M. pneumoniae-associated mucositis or M. pneumoniae-induced rash and mucositis separately from Stevens-Johnson syndrome, is argued in the dermatological manifestations. Serological methods are recommended for diagnosis because pneumonia or respiratory symptoms are often minimal or even absent in extrapulmonary manifestations due to M. pneumoniae infection. Concomitant use of immunomodulators, such as corticosteroids or immunoglobulins with antibiotics effective against M. pneumoniae, can be considered as treatment modalities for most severe cases, such as encephalitis. Further studies would be necessary to construct a comprehensive therapeutic strategy, covering microbiology (antibiotics), immunology (immunomodulators), and hematology (anticoagulants). The possible influence of the emergence of macrolide-resistant M. pneumoniae on extrapulmonary manifestations, which can be considered of limited clinical threat in Japan where the resistant rate has currently decreased, is discussed on the basis of unique biological characteristics of M. pneumoniae, the smallest self-replicating organism.